Digital Cultural Tourism Promotion Training as a Pillar of Creative Economy Village in Sei Gohong Village, Palangka Raya City: Pelatihan Promosi Digital Cultural Tourism Sebagai Pilar Kelurahan Ekonomi Kreatif Di Kelurahan Sei Gohong, Kota Palangka Raya - Romadoni, Muhamad; Harinie , Luluk Tri; Girindraswari, Nawung Asmoro; Asang, Daniel Batuah Barajaki; F, Vitani Desy Derja (Dinamisia : Jurnal Pengabdian Kepada Masyarakat, 2025)
Sei Gohong Village is a tourist area that has local potential to support creative economy programs through digital-based promotion. The goal is to develop Human Resources (HR) in implementing the use of technology in realizing the creative economy village pillar program through cultural tourism. The method used in community empowerment activities uses a collaborative learning model, including training in video content creation and digital promotion to introduce cultural tourism. The results of the activities showed an increase in community skills in creating video content and running digital promotions, with an 85% increase in participant understanding based on post-test results. This program proves the importance of digitalization in the development of culture-based tourism as a pillar of the creative economy. Further programs are needed to improve content creativity and expand the scope of promotion through digital platforms. The role of youth organizations and pokdarwis as the driving force in promoting tourism is evidence of the readiness of sustainable human resources in running the program